Integration of six sigma with lean production: an analysis through multiple cases - Thiago Henrique Pinheiro; Alisson Christian Scheller; Paulo A Cauchick Miguel (Revista Produção Online, 2013)
The intense competition between markets has taken companies, regardless of their size, to implement one or more quality improvement programs. One of the main purposes of these programs is the enhancement of company effectiveness and efficiency. There is today a growing interested in a proposal named Lean Six Sigma. Their objective is to apply six sigma concepts integrated with Lean Production. A model named Lean Six Sigma has raised interest, once its objective is to apply the concepts of the Six Sigma program integrating them with the principles of Lean Production. Six Sigma contributes with methods for problem identification, measurement and analysis, and the Lean Production offers techniques and procedures applied to reduce waste in the production. In this context, this paper aims at demonstrating the results of a field research, from which purpose was to identify relevant factors for Six Sigma implementation combined with Lean Production. To meet these objectives, three organizations from different industrial sectors were investigated. It was verified that in two of those companies, the programs were successfully implemented. Based on data analysis, it is possible to identify that one of the major difficulties encountered by the program leaders is related to the company’s human resources infra-structure. It is necessary to take into account that the conclusions are limited to a small sample of three units of analysis. However, this work offers the possibility of an analytical generalization.